Kompetensi Profesional Guru dalam Mengembangkan Pembelajaran Diferensiasi pada Mata Pelajaran Bahasa Indonesia (Penelitian Kualitatif di Kelas V SDIT Atikah Musaddad Garut) - Elis Parida; Iis Komariah; Ade Holis; Masripah (PT PUBLIKASI INSPIRASI INDONESIA, 2026)
This study aims to explore teachers' professional competencies in developing differentiated learning in fifth-grade Indonesian language at SDIT Atikah Musaddad. The findings highlight several crucial aspects of teacher competency in developing differentiated learning, including the ability to adapt learning materials to students' needs, the use of diverse assessment strategies, and skills in managing inclusive classroom interactions. The research method used was a qualitative approach with a case study as the primary design. Data were collected through classroom observations, in-depth interviews with Indonesian language teachers, and analysis of lesson plan documents and teaching materials. Data analysis was conducted using thematic analysis techniques to identify differentiation practices implemented by teachers in teaching Indonesian language. The implications of this study are the importance of teacher professional development at SDIT Atikah Musaddad, with an emphasis on the application of differentiation practices to facilitate more effective and inclusive learning in the context of fifth-grade Indonesian language classes. Thus, this research is expected to provide valuable insights for curriculum development and teacher training to improve Indonesian language learning outcomes at the elementary school level.